Los imaginarios que tienen los padres de familia sobre el uso de los recursos tecnológicos en la formación de sus hijos (2017)
The imaginaries have been a topic that frequently the social disciplines have studied; well they show the personal perception about the reality of him, of the other and of the world. Considering the previous, it’s important show to prove in the family the interpretations about the topics, especially of the technological resources, for two important aspects; one, the family is the principal core of the society and the family is the first agent of formation of beliefs and two, everybody is exposed to use the technology. For the purpose to prove the imaginaries that parents have about the using of the technological resources in the formation of their children, it made an investigation Through case study strategy (2), using, the interactive technique (colcha de retazos), a deep interview and direct observation. An important aspect in the imaginaries, it was related with breeding model with respect to the using of the technological resources, it shows that the education that the parents provides to their children must be based in the familiar unity and the high quality time. Likewise, the parents believe that they aren’t formed and prepared for to confront the technologic advances, insomuch as the children have knowledge higher than they and for this, it can bring on difficulties at the moment to take the control of these devices, offsetting this, with the belief that the technological resource is an exclusive medium to strengthen the children´s learning.